TEACHING AUTHENTIC READING MATERIALS FOR HIGH LEVEL STUDENTS - Rakhimakhon Tursunova Valijonovna (TADQIQOTLAR, 2025)
Annotation. This article explores effective methods of teaching reading using authentic  materials  for  high-level  students.  Authentic  texts,  taken  from  real-life sources,  help  learners  develop  natural  language  use,  critical  thinking,  and communicative  competence.  The  study  also  discusses  how  teachers  can  select  and apply  authentic  materials  in  class  to  enhance  vocabulary,  motivation,  and comprehension skills.